Transferência e contratransferência em “O Príncipe das Marés” : aplicação de conceitos psicanalíticos - Silva, Claudia Regina Furini da (2011)
The present dissertation is compound of two studies, according to the rules of the Post-Graduation Psychology Program of PUCRS. The first one is a literature review of Transference and Countertransference with the aim of examining such concepts over the years of conceptual theorization in Psychoanalysis. For this study bibliographic search was performed in Scielo, Lilacs, PsycInfo e IndexPsi, in order to obtain articles about the mentioned concepts, using the keywords transference and countertransference; books were much used. The concept of transference did not suffer much modification but the concept of countertransference: regarded by Freud as an annoyance to the work of analysis, it was understood later on as a useful tool in the analysis if the contratransferencial situation if well understood by the analyst. The second study regards the application of the concepts of transference and countertransference to the book/film “The Prince of Tides”. In order to do so the book/film was read/seen and with the book a content analysis was performed aiming at identifying moments in which transference and countertransference were in action in the therapist/patient relationship, and with such moments the pertinent theoretical reflection was done. The rich material delivered by book/film allowed illustrating well the transference and countertransference variation that is: positive, negative and erotic transference and countertransference situations lived by the therapeutic pair.